Disease Burden in Osteoarthritis Is Similar to That of Rheumatoid Arthritis at Initial Rheumatology Visit and Significantly Greater Six Months Later. Issue 8 (3rd July 2019) - Chua, Jacquelin R.; Jamal, Shakeel; Riad, Mariam; Castrejon, Isabel; Malfait, Anne‐Marie; Block, Joel A.; Pincus, Theodore
Abstract : Objective: To analyze disease burden in osteoarthritis (OA) according to Multidimensional Health Assessment Questionnaire (MDHAQ)/Routine Assessment of Patient Index Data 3 (RAPID3) scores at the initial visit and the 6‐month follow‐up visit, compared with rheumatoid arthritis (RA) as a benchmark for high disease burden. Methods: All patients with all diagnoses at the Rush University Medical Center Division of Rheumatology complete a paper MDHAQ at all visits, saved as a PDF in the electronic health record. MDHAQ 0–10 scores for physical function, pain, and patient global assessment (compiled into RAPID3 0–30 scores) and additional scales at the initial and 6‐month follow‐up visits, for new OA and RA patients seen from 2011 to 2017, were compared. OA and RA patients were classified as self‐referred or physician‐referred, and RA patients were classified as disease‐modifying antirheumatic drug (DMARD)–naive or having prior‐DMARD treatment. Patient groups were compared using t ‐tests and analysis of variance, adjusted for age, disease duration, body mass index (BMI), education, and ethnicity. Results: Compared with RA patients, OA patients had higher age, BMI, and disease duration. At initial visit, the mean RAPID3 did not differ significantly in OA versus DMARD‐naive RA patients, whether self‐ or physician‐referred (range 14.8–16.4 [ P = 0.38]), or in all OA patients versus DMARD‐naive RA patients versus prior‐DMARD RA patients (15.0, 15.7, and 15.8, respectively [ P = 0.49]). After 6 months, RAPID3 was improved to 13.3, 10.3, and 10.8, respectively, which represented substantially greater improvement in RA patients than OA patients ( P < 0.001). Similar results were seen for most self‐reported measures and in adjusted analyses. Conclusion: MDHAQ/RAPID3 scores are similar in OA and RA patients at the initial visit, but higher in OA patients than in RA patients 6 months later, reflecting superior RA treatments. The same MDHAQ/RAPID3 allows comparisons of disease burdens in different diseases.